2012
DOI: 10.1117/12.911641
|View full text |Cite
|
Sign up to set email alerts
|

Realistic simulation of breast mass appearance using random walk

Abstract: The aim of the present work was to develop a method for simulating breast lesions in digital mammographic images. Based on the visual appearance of real masses, three dimensional masses were created using a 3D random walk method where the choice of parameters (number of walks and number of steps) enables one to control the appearance of the simulated structure. This work is the first occasion that the random walk results have been combined with a model of digital mammographic imaging systems. This model takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The depth of insertion was arbitrarily selected within the breast thickness. The simulated DLA mass was inserted in a 2D mammogram using the method developed by Rashidnasab et al 5,7 which used a degradation model of the imaging system, taking into account the polychromatic nature of the X-ray spectra, local glandularity and the scatter around the insertion site. The corresponding insertion location and local glandularity estimation were then calculated for the DBT 0° projection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of insertion was arbitrarily selected within the breast thickness. The simulated DLA mass was inserted in a 2D mammogram using the method developed by Rashidnasab et al 5,7 which used a degradation model of the imaging system, taking into account the polychromatic nature of the X-ray spectra, local glandularity and the scatter around the insertion site. The corresponding insertion location and local glandularity estimation were then calculated for the DBT 0° projection.…”
Section: Methodsmentioning
confidence: 99%
“…Simulated masses were inserted into 2D mammograms using the method developed by Rashidnasab et al 5,7 as shown in Figure 1(left). The primary photon flux was calculated at each pixel before and after insertion using polychromatic X-ray spectra model (block 3).…”
Section: Insertion Of Simulated Masses In 2d Mammogramsmentioning
confidence: 99%
“…An initial experiment was conducted whereby the masses [6][7] and microcalcifications [8] were inserted into the breast phantom [5] by replacing the tissue voxels with lesion/micro-calcification voxels at appropriate locations. One mammogram and 15 tomosynthesis primary projections were acquired using the ray tracing tool [9], Beer's law and attenuation coefficients [10] corresponding to the appropriate X-ray spectrum [11], at different angles in accord with the Hologic specification.…”
Section: Methodsmentioning
confidence: 99%
“…The method of insertion into 2D-mammogram was adopted from Rashidnasab et al [6][7], and the method of insertion into tomosynthesis projections was adopted from Shaheen et al [8]. A series of templates were created from the projections of the lesion or microcalcifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation